Noteworthy prognostic value of phospholipase C delta genes in early stage pancreatic ductal adenocarcinoma patients after pancreaticoduodenectomy and potential molecular mechanisms. (6th December 2019) - Zhou, Xin; Liao, Xiwen; Wang, Xiangkun; Huang, Ketuan; Yang, Chengkun; Yu, Tingdong; Han, Chuangye; Zhu, Guangzhi; Su, Hao; Han, Quanfa; Chen, Zijun; Huang, Jianlv; et al.
Abstract: The purpose of this investigation was to explore the prognostic value of phospholipase C delta (PLCD) genes in early stage pancreatic ductal adenocarcinoma (PDAC) and its potential molecular mechanisms. The prognostic value of PLCD genes in early stage PDAC was assessed using the Kaplan‐Meier method and multivariate Cox proportional hazards regression model. Genome‐wide correlation analysis was performed on PLCD3 to identify the highly correlated genes in the transcriptome. Then, PLCD3 and these correlated genes together underwent a bioinformatics analysis to elucidate the potential molecular biological functions of PLCD3 in PDAC. PLCD1 and PLCD3 are significantly overexpressed in PDAC. In PDAC patients, PLCD3 is overexpressed in certain groups of people with a history of alcoholism ( P  = .032). High expression of PLCD3 was found to be associated with lower overall survival (OS) of patients with early stage PDAC ( P  = .020; adjusted P  = .016). A combination of PLCD3 and clinical variables was able to better predict the outcome of patients with early stage PDAC. These clinical variables are histological grade ( P  = .001; adjusted P  = .001), targeted molecular therapy ( P  < .001; adjusted P  < .001), radiation therapy ( P  = .002; adjusted P  = .039), and residual resection ( P  = .001; adjusted P  = .002). The bioinformatics analysis revealed that PLCD3 is associated with angiogenesis, intracellular signal transduction, and regulation of cell proliferation. In conclusion, PLCD3 may be a potential prognostic biomarker for early stage PDAC. Abstract : In our investigation, PLCD1 and PLCD3 were found to be high expressed in PAAD tumor tissue compared with normal tissue. We also discovered that PDAC patients who drank alcohol had higher levels of PLCD3 than those without alcohol history. PLCD3 might be potential prognostic biomarkers for early stage PDAC according to the result of survival analysis. But in stratification analysis, PLCD3 was associated with OS only when early stage PDAC patients were in the age >60 group, female gender group, alcohol history group, low histologic grade group, with radiation therapy group, or R0 residual resection group.